2013
DOI: 10.1167/iovs.13-12999
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Baseline Human Corneal Subbasal Nerve Density for Clinical Investigations With Laser-Scanning in Vivo Confocal Microscopy

Abstract: A baseline human corneal subbasal nerve density has been determined by laser-scanning IVCM using rigorous methods. The methods and results could aid in the future assessment of corneal nerves in various patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 38 publications
5
64
5
2
Order By: Relevance
“…Quantitative assessment of CNFL is regarded as the single most reliable parameter of SBP structural and functional integrity. 24 In the present study, using our quantification software, the mean CNFL value in the IVCM images (21.7 17 The median CNFL values calculated in this study by histology is approximately two times greater than previous high estimates (21.6 ± 5.98 and 25.9 ± 7.0 mm/mm 2 ) based on IVCM observations. 25,26 One explanation for these higher values seen by histology is that the immunochemical staining method dependably detects small diameter sub-basal nerves and interconnecting axons that are too thin or faint to be imaged reliably by IVCM.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Quantitative assessment of CNFL is regarded as the single most reliable parameter of SBP structural and functional integrity. 24 In the present study, using our quantification software, the mean CNFL value in the IVCM images (21.7 17 The median CNFL values calculated in this study by histology is approximately two times greater than previous high estimates (21.6 ± 5.98 and 25.9 ± 7.0 mm/mm 2 ) based on IVCM observations. 25,26 One explanation for these higher values seen by histology is that the immunochemical staining method dependably detects small diameter sub-basal nerves and interconnecting axons that are too thin or faint to be imaged reliably by IVCM.…”
Section: Discussioncontrasting
confidence: 47%
“…25,26 One explanation for these higher values seen by histology is that the immunochemical staining method dependably detects small diameter sub-basal nerves and interconnecting axons that are too thin or faint to be imaged reliably by IVCM. 24 IVCM, with a limited lateral resolution of 1-2 μm, 27 enables enface imaging of the SBP and its nerve fiber bundles. In contrast, the β-III-tubulin immunohistochemical staining method, by exploiting the phenomenon of histochemical amplification of the avidin-biotinhorseradish peroxidase complex methodology and a strong 'signal to noise' ratio, is able to detect more minute patterns of corneal SBP anatomy including very small diameter nerve fiber bundles, interconnecting single nerve fiber branches and their connection points (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies also typically include subjects widely varying in age, although age is known to impact the SBP. 17,20 Moreover, an image sampling-based strategy is sensitive to selection criteria, the disease state of the SBP, and observer experience/masking. As a result, nerve fiber length density values in various cohorts differ across studies, and it has been noted in systematic reviews that better standardization of methods is required for clinical adoption of IVCM to assess pathologic levels of nerve length density.…”
Section: Resultsmentioning
confidence: 99%
“…Raw image sets obtained by IVCM examination underwent processing by automated methods to produce depth-corrected widearea mosaics with continuous nerve fiber paths and nerve and background intensity levels, as previously reported. 4 Also, nerves in mosaics were traced both manually and by a fully automated method 20 to quantify the total mosaic nerve fiber length density (mCNFL) and nerve fiber length density in the inferocentral whorl region (wCNFL). The total length of all traced nerves in a mosaic was divided by the mosaic area containing subbasal plexus in mm 2 , yielding the mosaic corneal subbasal nerve fiber length density (mCNFL) in mm/ mm 2 .…”
Section: Confocal Microscopy and Mosaic Image Generation And Analysismentioning
confidence: 99%
“…Other studies evaluating the density of fibers per field are shown in Table 3 4, 10,11,12 . Only studies using the same methodology employed here were included.…”
Section: Discussionmentioning
confidence: 99%